Performance analysis of scheduling algorithms in Next Generation Networks (2010)
QoS in Convergent networks is widely discussed item in IP networks. But with the implementation of the Next Generation Networks by most operators around the world, QoS for different services and applications must fulfill. In order to deal with this problem, we simulate end to end QoS parameters, according to lTV Y.1540 and Y.1541 recommendations and different scheduling algorithms proposed by manufacturers and the literature. In this paper we show the results for such simulations for voice over IP service in different load conditions.